Changing Trend in Plant Nutrition for crop production - Basak, Nirmalendu; Datta, Ashim; Mandal, Biswapati; Chaudhari, S. K.; Sharma, D. K. (Indian Farming, 2016)
For our country, there is an urgent need to narrow down the wide ratio of N, P and K consumption by stepping up P and K usage, which suffered markedly after 1990. By doing so, food security will be safeguarded and agricultural practices will be more sustainable and profitable. There is a need for all stakeholders to join hands together to meet the challenges of improving income from farming and make Indian farmers globally competitive.